Lynching and Leisure : Race and the Transformation of Mob Violence in Texas - Scott, Terry Anne (Book collections on Project MUSE., 2022)
"Comprehensive study that traces how lynchings in Texas evolved from largely clandestine acts into racialized recreation in which crowd involvement became integral to the atrocities committed"--